Kosmetik Ilegal, Otoritas Pengawasan, dan Profesi Medis: Kajian Hukum Administrasi di Indonesia - Firmantoro, Kiki; Suvinah, Suvinah (PT Elaborium Elevasi Indonesia, 2025)
The circulation of illegal cosmetics in Indonesia has increased significantly in the past five years, with the value of the recovered products reaching tens of billions of rupiah. This phenomenon becomes even more complex when the perpetrators are medical professionals who are supposed to maintain public health standards. This study aims to analyze the legal and administrative responsibilities of medical professionals who distribute cosmetics without a distribution permit and examine the roles of the Indonesian Food and Drug Monitoring Agency (BPOM) and the Indonesian Medical Disciplinary Council (MKDKI). The research method uses a normative juridical approach with case analysis and regulatory comparison. The primary legal materials include Law Number 36 of 2009 concerning Health, Law Number 8 of 1999 concerning Consumer Protection, and regulations related to medical practice, supported by an analysis of 15 court decisions from 2019-2024. The results show a significant disparity between the threat of sanctions in regulations (fines of up to IDR 1 billion) and the reality of court decisions (averaging IDR 5-10 million). BPOM's authority remains limited to administrative and supervisory matters, while MKDKI has a role in imposing professional disciplinary sanctions. Regulatory disharmony and weak coordination between authorities create legal loopholes that allow medical personnel to engage in illegal practices. This study recommends regulatory harmonization through the establishment of a cross-ministerial task force, strengthening progressive administrative sanctions, and implementing an integrated monitoring system to protect consumers and maintain the integrity of the medical profession.